A composição de teleostei e elasmobranchii no holoceno brasileiro, baía Babitonga/SC: suporte para referências ecológicas - Fossile, Thiago (2019)
Small-scale fisheries contribute to food security and poverty eradication by providing food, income and employment for millions of people. However, among some problems, the sector suffers from declining biological resources and degraded aquatic habitats, impacting coastal and small-scale fishers who depend on local and regional ecosystems to derive their subsistence. Based on the concept of Shifting Baselines Syndrome, there are no adequate reference points for analysis of changes in fish composition, as subsidies for adequate management of fishery. Therefore, it is necessary to study historical and archaeological data with the objective of identifying change and spatial-temporal evolution of the species (e.g. overfishing). This study aimed to describe the ichthyofauna diversity in Brazilian pre-Columbian and to contribute to the development of ecological references, from the identification and measurement of faunistic remains in archaeological sites in Babitonga Bay for the purpose of comparison with information about the fisheries in the Brazilian coast.